2017
DOI: 10.3390/ijms18020291
|View full text |Cite
|
Sign up to set email alerts
|

A Mixture of Persistent Organic Pollutants and Perfluorooctanesulfonic Acid Induces Similar Behavioural Responses, but Different Gene Expression Profiles in Zebrafish Larvae

Abstract: Persistent organic pollutants (POPs) are widespread in the environment and some may be neurotoxic. As we are exposed to complex mixtures of POPs, we aimed to investigate how a POP mixture based on Scandinavian human blood data affects behaviour and neurodevelopment during early life in zebrafish. Embryos/larvae were exposed to a series of sub-lethal doses and behaviour was examined at 96 h post fertilization (hpf). In order to determine the sensitivity window to the POP mixture, exposure models of 6 to 48 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 68 publications
3
22
0
Order By: Relevance
“…However, although the pattern of the hyperactivity was identical across studies for PFOS with observed hyperactivity in the L1, L2, and D1 periods, it varied following exposure to PFHxS, where elevated locomotor activity was observed in the L1, L2, and D1 periods in Study 1 and the L2, D1, and D2 periods in Study 3. Regardless, in line with previously published work (Huang et al 2010;Khezri et al 2017;Spulber et al 2014), exposure to nonteratogenic concentrations of PFOS or PFHxS consistently triggered behavioral hyperactivity. Although more work is needed to understand the biological relevance of disparate xenobiotic-induced locomotor activity phenotypes, this represents a powerful approach for grouping chemicals based on shared toxicity phenotypes.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…However, although the pattern of the hyperactivity was identical across studies for PFOS with observed hyperactivity in the L1, L2, and D1 periods, it varied following exposure to PFHxS, where elevated locomotor activity was observed in the L1, L2, and D1 periods in Study 1 and the L2, D1, and D2 periods in Study 3. Regardless, in line with previously published work (Huang et al 2010;Khezri et al 2017;Spulber et al 2014), exposure to nonteratogenic concentrations of PFOS or PFHxS consistently triggered behavioral hyperactivity. Although more work is needed to understand the biological relevance of disparate xenobiotic-induced locomotor activity phenotypes, this represents a powerful approach for grouping chemicals based on shared toxicity phenotypes.…”
Section: Discussionsupporting
confidence: 88%
“…Compared with previously reported morphological and behavioral effects following exposure to PFBS, PFHxS, PFOS, or PFHxA (summarized in Table 5) (Hagenaars et al 2011;Huang et al 2010;Jantzen et al 2016;Khezri et al 2017;Padilla et al 2012;Spulber et al 2014;Truong et al 2014;Ulhaq et al 2013aUlhaq et al , 2013b, this study expanded our understanding of aliphatic PFAS toxicity to include data on PFPeS and PFHpS for the first time and reported novel results for PFHxA and PFHxS. Although not systematically designed to test a specific PFAS R-group (i.e., sulfonic or carboxylic acids), Ulhaq et al (2013a) tested 4-, 8-, 9-, and 10-carbon carboxylic acid aliphatic PFAS and 4-and 8-carbon sulfonic acid aliphatic PFAS in a zebrafish developmental toxicity assay and proposed the idea that carbon chain length may be a determinant of PFAS toxicity in zebrafish.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Several studies have reported that analysis of the swimming activity of larval stages of fish could provide predictions of mechanisms of action of unknown or less known compounds [13][14][15][16][17]. Behavioural studies using automatic video tracking systems have been shown to be successful for toxicity screening of different contaminants, like endocrine disrupting chemicals (EDCs), nanoparticles and metals [18,19], including complex mixtures [20][21][22]. Increasing recognition and use of behavioural endpoints in ecotoxicological studies is promoting interest for inclusion of behavioural effects as an alternative for lethal endpoints in environmental hazard assessment [12,23,24].…”
Section: Introductionmentioning
confidence: 99%